PENERAPAN MULTIMEDIA DEVELOPMENT LIFE CYCLE PADA GAME EDUKASI PEMBELAJARAN LAGU NASIONAL DAN LAGU DAERAH BERBASIS ANDROID - Diany; Ari Purno Wahyu Wibowo (Universitas Widyatama, 2021)
Educational game could act as learning media to increase desire and motivation to learn. Nowdays, national songs and folk songs in Indonesia are rarely heard and memorized by young generation, they prefer pop songs that are currently trendy. The pianica musical instrument is are rarely played, besides that the number of anthusiasts to play the pianica intrument are relatively small. Meloquin is an educational game to increase interest in playing pianica instrument while to increase knowledge in recoqnizing and remembering the national anthem in indonesia. The development of this game applies the Multimedia Development Life Cycle (MDLC) method consisting of six stage. In this application user can guess the song by playing the pianica according to the direction of song lyric notes that have been provided in each question. The test results for feasibiltiy of using this game is included 78% in the good category. Keywords : Educational Game, National Songs, Folks Song, Pianica.